UJI BAKTERIOLOGI BAKTERI ESCHERICHIA COLI PADA AIR MINUM ISI ULANG DI RUMAH MAKAN DI KELURAHAN JATI, KOTA PADANG, INDONESIA - Bawahi, Badrul Amin Bin (SINERGI : Jurnal Riset Ilmiah, 2025)
Water covers more than two-thirds of the earth's surface, but most of it is salty and undrinkable. Available fresh water sources are only 2.7% of the available water on earth but only 1% of fresh water is available (in lakes, rivers and groundwater) and is accessible. Most of the available freshwater resources are inaccessible because they are located in hidden hydrological parts of the cycle (deep aquifers) and in glaciers (frozen in polar ice), which means it is safe to drink water on earth has a very small proportion (~3% ) in freshwater resources. The purpose of this study was to determine the presence of contamination and the presence of bacteria in refilled drinking water at a restaurant in Jati Sub-district, Padang City, Indonesia. This research is descriptive in nature which provides an overview of the identification of bacteria in refilled drinking water at a restaurant in Jati Village, Padang City, Indonesia. Samples were taken as many as 25 samples. Sampling was carried out directly with sterile bottles from plastic wrap, while data were analyzed using MPN 5-1-1 tables and continued with the presence of colonies of E.coli bacteria from drinking water samples. The results of this study obtained 7 samples (28%) did not contain Coliforms bacteria, 6 samples (24%) with poor water quality with MPN index (1- 50/100ml), 1 sample (4%) with water quality poor drinking water with MPN index (51-100/100ml), and 11 samples (44%) with very poor water quality with MPN index (≥100/100ml). Of the 18 samples, only 2 samples were found to have E.coli bacteria. Based on the results of this study, it was concluded that 18 of the 25 samples studied contained Coliforms bacteria and did not meet the microbiological requirements of drinking water. Of the 18 samples containing Coliforms bacteria, only 2 of 18 samples contained Escherichia coli bacteria